A study on sound barrier for noise control in Malaysia / Nor Amira Ruslan - Ruslan, Nor Amira (Faculty Architecture, Planninng and Surveying, 2015)
In this dissertation, it will be discussed regarding to sound barrier in Malaysia. The concern is about the noise pollution occurred especially at inhabitant area such as residential, schools,mosque and factories. It becomes priority to get to know about the sound level at those areas because noise can cause disturbance to community’s privacy, comfort and performances.Therefore, the focus of this study more likes to know the effective of the sound barrier at those areas. Thus, there are two methods to achieve this study, theoretical and experimental methods. Hence, it started from general introduction to this topic and it will be discussed on literature review. In literature review, it will emphasize respect to consideration elements on implementation of sound barrier. For experimental method, two case studies have been chosen to conduct the sound level test. The testing conducted at Section 19, Shah Alam and Taman Pemnata, Kuala Lumpur. By analyze the collection data and compared it with the theoretical information, the results has been proved that sound barrier at Section 19 was less effective than Taman Permata, this is because Section 19 do not used enough vegetation as natural noise absorber